Primary Multicentric Pulmonary Low-grade Fibromyxoid Sarcoma and Chelonid Alphaherpesvirus 5 Detection in a Leatherback Sea Turtle (Dermochelys coriacea). (April 2019) - Díaz-Delgado, J.; Gomes-Borges, J.C.; Silveira, A. Monteiro; Einhardt-Vergara, J.; Groch, K.R.; Cirqueira, C.S.; Sansone, M.; Gattamorta, M.A.; Matushima, E.R.; Catão-Dias, J.L.
Summary: We describe the gross, microscopical, histochemical and immunohistochemical features of a sclerosing pneumopathic disease process resembling primary multicentric pulmonary low-grade fibromyxoid sarcoma in a juvenile female leatherback sea turtle ( Dermochelys coriacea ). The animal was fresh, presented in good body condition and stranded dead in Aracaju, Sergipe state, Brazil, in September, 2017. Grossly, the lungs were enlarged bilaterally and the parenchyma was replaced by large, coalescing, white, firm masses that extended into the bronchi and bronchioles and to the pleura. Microscopically, these masses consisted of paucicellular populations of well-differentiated, spindle-shaped fibroblasts with low pleomorphism and low mitotic count, but tissue invasion. Abundant collagen in compact areas merged with peripheral fibromyxoid foci and inflamed stroma. Antibodies specific for cytokeratins AE1/AE3 and smooth muscle actin (SMA) labelled pneumocytes lining the remaining distorted alveoli and the hypertrophied and hyperplastic bronchial muscles, respectively. Tumour cells were negative for SMA; neither neoplastic nor normal tissues cross-reacted with antibodies specific for vimentin or Ki67. Chelonid alphaherpesvirus 5 (ChHV5) polymerase chain reaction analysis from formalin-fixed, paraffin wax-embedded lung tissue sections amplified a 450 base pair fragment of DNA-polymerase (UL30 region) that had 100% homology to sequences previously detected in green sea turtles ( Chelonia mydas ) on the Brazilian coast. Enterocolitis was a concomitant condition that likely caused morbidity in this case. These findings contribute to the body of knowledge on sea turtle health and expand the known geographical range for ChHV5 in the southern hemisphere. Graphical abstract: Image 1